A synthetic anti-Frizzled antibody engineered for broadened specificity exhibits enhanced anti-tumor properties. Issue 8 (17th November 2018) - Pavlovic, Zvezdan; Adams, Jarrett J.; Blazer, Levi L.; Gakhal, Amandeep K.; Jarvik, Nick; Steinhart, Zachary; Robitaille, Mélanie; Mascall, Keith; Pan, James; Angers, Stephane; Moffat, Jason; Sidhu, Sachdev S.
ABSTRACT: Secreted Wnt ligands play a major role in the development and progression of many cancers by modulating signaling through cell-surface Frizzled receptors (FZDs). In order to achieve maximal effect on Wnt signaling by targeting the cell surface, we developed a synthetic antibody targeting six of the 10 human FZDs. We first identified an anti-FZD antagonist antibody (F2) with a specificity profile matching that of OMP-18R5, a monoclonal antibody that inhibits growth of many cancers by targeting FZD7, FZD1, FZD2, FZD5 and FZD8. We then used combinatorial antibody engineering by phage display to develop a variant antibody F2.A with specificity broadened to include FZD4. We confirmed that F2.A blocked binding of Wnt ligands, but not binding of Norrin, a ligand that also activates FZD4. Importantly, F2.A proved to be much more efficacious than either OMP-18R5 or F2 in inhibiting the growth of multiple RNF43 -mutant pancreatic ductal adenocarcinoma cell lines, including patient-derived cells.